Upright head roll test: A new contribution for the diagnosis of lateral semicircular canal benign paroxysmal positional vertigo - Malara, Pasquale (Audiol Res, 2020)
Diagnosing the affected side in Benign Paroxysmal Positional Vertigo (BPPV) involving the Lateral Semicircular Canal (LSC) is often challenging and uncomfortable in patients with recent onset of vertigo and intense autonomic symptoms. The Minimum Stimulus Strategy (MSS) aims to diagnose side and canal involved by BPPV causing as little discomfort as possible to the patient. The strategy applied for LSC-BPPV includes the evaluation of pseudo-spontaneous nystagmus and oculomotor responses to the Head Pitch Test (HPT) in upright position, to the seated-supine test and to the Head Yaw Test (HYT) while supine. Matching data obtained by these tests enables clinicians to diagnose the affected side in LSC-BPPV. The purpose of this preliminary study is to propose a new diagnostic test for LSC-BPPV complimentary to the HPT, the Upright Head Roll Test (UHRT), to easily determine the affected ear and the involved arm in the sitting position and to evaluate its efficiency. Our results suggest that the UHRT can increase the sensitivity of the MSS without resorting to the HYT, thus reducing patient’s discomfort.